2015
DOI: 10.1002/phar.1648
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acarbose on Glycemic Variability in Patients with Poorly Controlled Type 2 Diabetes Mellitus Receiving Stable Background Therapy: A Placebo‐Controlled Trial

Abstract: The addition of acarbose to metformin and vildagliptin background therapy in patients with inadequately controlled type 2 diabetes decreased intraday glycemic variability, especially postprandial variability, but it was not associated with a significant change in interday glycemic variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…In comparative clinical studies, significant reductions in GV have been demonstrated with the GLP-1 RAs exenatide, liraglutide and lixisenatide when added to background therapy of oral antidiabetes drugs or high-dose basal-bolus therapy (Table 2). 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58 The DPP-4 inhibitors sitagliptin 53 and vildagliptin 54 significantly reduced GV compared with glimepiride and pioglitazone, respectively, in patients with T2D not adequately controlled on metformin monotherapy, 53, 54 while saxagliptin showed no difference in GV reductions compared with the alpha-glucosidase inhibitor acarbose, 52 which has known PPG-lowering effects (Table 2). 47, 48,49, 50, 51, 52, 53, 54, 55, 56, 57, 58…”
Section: Effects Of Diabetes Medications On Gvmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparative clinical studies, significant reductions in GV have been demonstrated with the GLP-1 RAs exenatide, liraglutide and lixisenatide when added to background therapy of oral antidiabetes drugs or high-dose basal-bolus therapy (Table 2). 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58 The DPP-4 inhibitors sitagliptin 53 and vildagliptin 54 significantly reduced GV compared with glimepiride and pioglitazone, respectively, in patients with T2D not adequately controlled on metformin monotherapy, 53, 54 while saxagliptin showed no difference in GV reductions compared with the alpha-glucosidase inhibitor acarbose, 52 which has known PPG-lowering effects (Table 2). 47, 48,49, 50, 51, 52, 53, 54, 55, 56, 57, 58…”
Section: Effects Of Diabetes Medications On Gvmentioning
confidence: 99%
“…57 Similarly, insulin detemir did not differ in terms of effect on GV compared with insulin glargine (Table 2). 47, 48, 49, 50, 51, 52, 53,54, 55, 56, 57, 58…”
Section: Effects Of Diabetes Medications On Gvmentioning
confidence: 99%
“…The glycemic effects of saxagliptin are mediated by glucose‐dependent stimulation of insulin secretion and suppression of glucagon 21 , which has been shown to effectively control the glycemic variability 22‐25 . Although acarbose was also shown to reduce several parameters of glycemic variability 26,27 , the current study showed that its efficacy on blood glucose levels appears to diminish at higher baseline HbA1c levels. This could be due to its non‐insulin‐dependent mechanism of action, which is non‐systemic and limited to delaying the intestinal glucose absorption, and is therefore independent of the baseline hyperglycemia.…”
Section: Discussionmentioning
confidence: 58%
“…The technology has, however, also been judged mature enough to be used as a tool for the assessment of glycemic variation when using different glucose-lowering interventions in people with type 1 or type 2 diabetes. [46][47][48][49][50][51][52] and continues to improve. As the devices provide repeated glucose estimates at very short intervals, a wide variety of derived glycemic status parameters can and have been used for reporting purposes.…”
Section: Metricsmentioning
confidence: 99%
“…51,52 Thus, some studies use historical parameters such as the MAGE, standard deviation (SD) or coefficient of variation about mean plasma glucose level, or the mean of daily difference (MODD). 40 Meanwhile, others use mean glucose level, low/high blood glucose indices, the percentage of time over/under a certain glucose level, the time in target, 32,36 the AUC at certain time points of defined glucose levels, the mean subsequent sensor glucose nadir, the median time to post-prandial peak glucose levels, or the number of excursions above and below some level 19,22,[46][47][48]50 (Table 2). This variability of reporting parameters presently makes comparisons of CGM results between studies difficult, thus limiting generalizability and preventing comparisons among trials, including formal meta-analysis and network analysis.…”
Section: Metricsmentioning
confidence: 99%